The Influence of Compensation and Education Level on Air Traffic Controllers’ Performance at Jakarta Air Traffic Service Center (Perum LPPNPI) - Abdul Aziz Rachman; Dhian Supardam; Rahmawati Sukra (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the influence of compensation and educational level on the performance of air traffic controllers at Perum LPPNPI Jakarta Air Traffic Service Center. The performance of air traffic controllers plays a crucial role in maintaining aviation safety and operational efficiency; therefore, enhancing human resource quality is essential. The research employed a quantitative method with a survey approach involving 40 respondents from a total population of 400 employees. The independent variables consist of compensation (financial and non-financial) and educational level (education level, field relevance, and competence), while the dependent variable is performance, measured through quantity, quality, and punctuality indicators. The findings reveal that both compensation and educational level have a positive and significant effect on air traffic controllers’ performance, either partially or simultaneously. These results emphasize the importance of fair compensation and continuous educational and training development to improve employee performance. In conclusion, enhancing welfare and educational competence among air traffic controllers serves as an effective strategy to strengthen professionalism and aviation safety in Indonesia.